Need for and extent of lymph node dissection for upper tract urothelial carcinoma: an updated review in 2023 - Yanagisawa, Takafumi; Kawada, Tatsushi; von Deimling, Markus; Laukhtina, Ekaterina; Kimura, Takahiro; Shariat, Shahrokh F (Current opinion in urology, 2023)
PURPOSE OF REVIEW: Although lymph node dissection (LND) during radical nephroureterectomy (RNU) is recommended for high-risk nonmetastatic upper tract urothelial carcinoma (UTUC), adherence to guidelines remains insufficient in clinical practice. Therefore, this review aims to comprehensively summarize the current evidence regarding the diagnostic, prognostic, and therapeutic impact of LND during RNU in UTUC patients. RECENT FINDINGS: Clinical nodal staging using conventional CT scan has low sensitivity (25%) and diagnostic accuracy [area under the curve (AUC): 0.58] in UTUC, suggesting the importance of LND for obtaining accurate N-staging. Patients with pathological node-positive (pN+) disease have poor disease-free survival (DFS), cancer-specific survival (CSS), and overall survival (OS) compared with those with pN0. In addition, population-based studies showed that patients who underwent LND improved CSS and OS than those who did not, even in patients who received adjuvant systemic therapy. The number of lymph nodes removed has also been shown to be associated with improved CSS and OS, even in pT0 patients. Template-based LND should be performed as the extent of lymph node is more important than the number of lymph nodes. Robot-assisted RNU may facilitate performing a meticulous LND compared with a laparoscopic approach. Postoperative complications such as lymphatic and/or chylous leakage are increased but adequately manageable. However, the current evidence is not supported by high-quality studies. SUMMARY: Based on the published data, LND during RNU is a standard procedure for high-risk nonmetastatic UTUC, owing to its diagnostic, staging, prognostic, and, potentially, therapeutic benefits. Template-based LND should be offered to all patients who are planned for RNU for high-risk nonmetastatic UTUC. Patients with pN+ disease are optimal candidates for adjuvant systemic therapy. Robot-assisted RNU may facilitate meticulous LND compared with laparoscopic RNU.
Keywords: lymfadenektomie; lidé; lymfatické uzliny; nádory močovodu; Lymph Node Excision; Nephroureterectomy; Ureteral Neoplasms; nefroureterektomie; Lymph Nodes; Urinary Bladder Neoplasms; Humans; retrospektivní studie; Carcinoma, Transitional Cell; karcinom z přechodných buněk; nádory močového měchýře; Retrospective Studies